2009
DOI: 10.1111/j.1525-1594.2009.00934.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Types of Neonatal Extracorporeal Life Support Systems With Pulsatile and Nonpulsatile Flow

Abstract: We compared the effects of two neonatal extracorporeal life support (ECLS) systems on circuit pressures and surplus hemodynamic energy levels in a simulated ECLS model. The clinical set-up included the Jostra HL-20 heart-lung machine, either the Medtronic ECMO (0800) or the MEDOS 800LT systems with company-provided circuit components, a 10 Fr arterial cannula, and a pseudo-patient. We tested the system in nonpulsatile and pulsatile flow modes at two flow rates using a 40/60 glycerin/water blood analog, for a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
1

Year Published

2010
2010
2025
2025

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 16 publications
1
28
1
Order By: Relevance
“…The silicone membrane is characterized by a long blood path and resultant high pressure gradient. Evaluation of the hollow‐fiber oxygenator in the laboratory demonstrated improved hemodynamics with decreased pressure drop across the hollow‐fiber membrane, indicating lower resistance to flow . The reduction in pressure should result in lower hemolysis and less inflammatory activation.…”
Section: Evolution Of Technologymentioning
confidence: 99%
“…The silicone membrane is characterized by a long blood path and resultant high pressure gradient. Evaluation of the hollow‐fiber oxygenator in the laboratory demonstrated improved hemodynamics with decreased pressure drop across the hollow‐fiber membrane, indicating lower resistance to flow . The reduction in pressure should result in lower hemolysis and less inflammatory activation.…”
Section: Evolution Of Technologymentioning
confidence: 99%
“…demonstrated that patients with continuous flow devices and patients with pulsatile flow devices have comparable renal function after LVAD implantation. Still, there is a longstanding debate over whether or not pulsatile flow provides better perfusion than nonpulsatile flow and what are or will be the long-term chronic effects of depulsation 7. We reported recently that reduced pulsatility resulting from a continuous-flow LVAD implantation induced periarteritis in the calf kidney 8.…”
Section: Discussionmentioning
confidence: 99%
“…For the oxygenator, we compared two neonatal ECLS circuits with the new PMP HFMO or the conventional silicone oxygenator (7); we also evaluated three different HFMOs in terms of perfusion quality (8). For the pump, we not only compared the magnetically levitated centrifugal pump to the conventional roller pump in regard to the hemodynamic energy delivery as well as the air bubble handling (9), but we also evaluated the mechanical performance between two widely used centrifugal pumps (10).…”
Section: Recent Laboratory Studies At the Penn State Hersheymentioning
confidence: 99%